Coordination of Advertising Free Riding in Hybrid Channel Supply Chain. (15th June 2016) - Sha, Jin; Wang, Aihu; Lv, Ting; Wu, Wenling
Abstract : Advertising is a crucial tool for demand creation and market expansion; enterprises in supply chain use it widely to increase sales and improve profits. But the homogeneity of products sold in hybrid channel supply chain magnifies the positive externalities of advertising and leads to serious free-riding problem. To coordinate the supply chain effectively, firstly, this paper classifies hybrid channel supply chain based on the relationship between members and selects horizontally integrated, vertically integrated, and decentralized hybrid channel supply chains as research objects. Then, a demand function considering the common effect of price and advertising is proposed and coordination schemes for different types of supply chains are designed. Finally, a sensitivity analysis is performed to assess the impact of parameters on coordination using orthogonal experiment.